KENAKALAN REMAJA DI ERA GLOBALISASI - Subhan Ihza Nuralam; Edy Soesanto; Muhammad Farikh Hidayat Julio (CV. ADIBA AISHA AMIRA, 2024)
Juvenile delinquency is something that is considered commonplace among young people today. Juvenile delinquent behavior is caused by 2 factors, namely factors from the teenager himself (internal) and from outside (external). The aim of this research is to identify factors that influence juvenile delinquency in the era of globalization. Research designs on juvenile delinquency in the era of globalization can be carried out using qualitative or quantitative methods. Based on the research results obtained on factors regarding the impact of globalization on juvenile delinquency, namely the bad influence of globalization on teenagers, technological developments, the challenges of globalization, the increasingly declining moral values of teenagers. Among these factors, the factors that most influence juvenile delinquency in the era of globalization are the influence of a bad environment and the influence of peers. This can be caused by the majority of them receiving bad behavior from their parents. Therefore, every parent is expected to provide a gentle and humorous attitude towards their teenage children and continue to control their teenage children's activities so that they are kept away from juvenile delinquency. (Budi Artini, 2018).